2019
DOI: 10.1111/vec.12859
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of the clinical presentation, magnetic resonance imaging findings, and outcome of dogs diagnosed with intracranial empyema (2008–2015): 9 cases

Abstract: Objective To describe the clinical presentation, advanced imaging findings, and short‐ and long‐term outcomes in dogs with intracranial empyema. Design Retrospective case series. Animals Client‐owned dogs diagnosed with intracranial empyema. Methods Medical records from 2 referral hospitals were searched for dogs diagnosed with intracranial empyema. To be included in this study, dogs had to fulfill 1 or more of the following 3 inclusion criteria: a magnetic resonance imaging (MRI) scan with space occupying acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(44 citation statements)
references
References 27 publications
4
38
2
Order By: Relevance
“…In agreement with the results of previous studies, elevated CSF TNCC, TP and neutrophilic pleocytosis can be identified in dogs with intracranial empyema 25,32 . Although the number of cases in this study was small, all dogs diagnosed with intracranial empyema had an increased TNCC, increased TP and abnormal cytology.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with the results of previous studies, elevated CSF TNCC, TP and neutrophilic pleocytosis can be identified in dogs with intracranial empyema 25,32 . Although the number of cases in this study was small, all dogs diagnosed with intracranial empyema had an increased TNCC, increased TP and abnormal cytology.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with the results of previous studies, elevated CSF TNCC, TP and neutrophilic pleocytosis can be identified in dogs with intracranial empyema. 25,32 Although the number of cases in this study was small, all dogs diagnosed with intracranial empyema had an increased TNCC, increased TP and abnormal cytology. Although further studies are necessary, this result could indicate the clinical usefulness of CSF analysis to diagnose intracranial empyema as a cause of vestibular syndrome in dogs.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The most unusual finding in our case was a compressive SFA, a MRI feature that is commonly associated with subdural empyema [ 20 ], traumatic [ 21 ] or non-traumatic hematoma [ 22 , 23 ] or as the result of overshunting after ventriculoperitoneal shunt insertion in dogs [ 24 ] but has never been described as MRI feature in CPCs. At the time of presentation, the underlying cause of this lesion was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Still, to date in veterinary medicine, the incidence and mortality are not well established [ 3 , 8 ]. The number of studies on SEE [ 3 , 4 , 8 , 11 , 12 , 16 ] and intracranial empyema [ 18 , 19 , 20 , 21 ] published in the last 15 years remains relatively low. In human medicine, the incidence of hospital admission for this condition has tripled [ 5 ], and the mortality rates are estimated at 5–16% worldwide, with less than 50% of surviving patients achieving full recovery [ 1 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%